Endovenous Photocoagulation Using a Diode Laser for Complicated Varicose Veins Related to Stasis Ulcers. (January 2019) - Lee, Jing-Syuan; Hsiao, Yen-Chang; Chang, Cheng-Jen
Abstract : Background: The objective of this study was to assess the efficacy and safety of endovenous laser photocoagulation (EVLP) at a wavelength of 810 nm for treating complicated venous insufficiency associated with venous ulcers. Materials and Methods: A retrospective review of 110 patients with 180 legs having chronic venous insufficiencies associated with varicose veins treated over an 8-year period was conducted. Patients ranged from 16 to 80 years of age and included 85 women and 25 men. Of the 110 patients, 32 (29.10%) patients with 40 legs having varicose veins were defined as having complicated varicose veins associated with venous ulcers. All 32 patients received EVLP treatment using a diode laser. Complications were evaluated at 3 weeks (early), 6 weeks (late), and 6 months (final) after EVLP treatment. The primary efficacy and final outcome measurement were determined through quantitative assessment using Hach's and clinical, etiological, anatomical, and pathophysiological classification. Safety was evaluated for each treatment group by monitoring adverse effects. Results: Early complications were swelling, local paresthesia, pigmentation, minor superficial thermal injury, superficial phlebitis, and localized hematomas. All complications and ulcerations resolved completely within 2 weeks. No recurrence occurred after the study's 6-month follow-up period. Based on paired t test analysis, clinically significant differences in severity scores were discovered, which were based on Hach's classification before and after EVLP treatment at a wavelength of 810 nm. All patients achieved improvement from clinical, etiological, anatomical, and pathophysiological class C6 to C5 . Permanent adverse effects were not observed. Conclusions: Endovenous laser photocoagulation at the wavelength of 810 nm permitted the use of appropriate light doses for treating complicated varicose veins associated with venous ulcers and resulted in significant improvement in lesions.